Optimizing Energy Industry E-Commerce Data Storage with Distributed File Systems and Cloud Computing - Müller-Schmidt, Alexander Heinrich; Rossi, Anna Maria; Bianchi, Mateo (Journal of Theory and Practice in Engineering and Technology, 2024)
This study explores the imperative of optimizing IoT data storage technology within the energy industry’s e-commerce sector. Amidst the proliferation of Internet of Things (IoT) devices generating vast and sequential data, efficient management becomes pivotal to mitigate transmission inefficiencies and system failures. The research demonstrates significant system performance and reliability enhancements by leveraging distributed file systems and cloud computing. Key optimizations include data fragmentation, replication, and load-balancing strategies, improving data processing efficiency and bolstering fault tolerance. Experimental results indicate a 50% increase in file uploading efficiency post-optimization, affirming the efficacy of these technological advancements in meeting escalating demands for robust, scalable data solutions.